Indian economy : essays on money and finance - Rangarajan, C. (Chakravarthy), 1932- (New Delhi : UBS Publishers' Distributors, 1998)
Lectures delivered during 1992-1997.
Includes bibliographical references and index.
Keywords: Monetary policy -- India; Banks and banking -- India; Rural development -- India